Kepercayaan diri remaja panti asuhan Aisyiyah dan implikasinya terhadap layanan Bimbingan dan Konseling - Monnalisza Monnalisza; Neviyarni S (Indonesian Institute for Counseling, Education and Therapy (IICET), 2018)
Low self-esteem is one of the problems experienced by orphanage adolescents. This study aims to describe adolescent self-confidence in terms of aspects of self-esteem, self-competence and feelings towards others. This research included in quantitative descriptive research. The study population was foster children in the Aisyyah Orphanage in Koto Tangah Branch, Padang, totaling 45 people. The sample uses purposive sampling. The results showed the level of adolescent confidence in the Aisyiyah Orphanage was in the moderate category. It was seen from the ability to judge themselves, comfort themselves, achieve perceived success, ability to deal with problems, problem-solving abilities, and feelings of being accepted by others, who were in the medium category, and indicators of feeling respected by others in the low category.